Interactive AR Application for Learning 3D Geometric Shapes in Elementary School: Aplikasi AR Interaktif untuk Pembelajaran Bentuk Geometris 3D di Sekolah Dasar - Ramadhan, Mochammad Hisyam Syah; Hindarto; Rosid, Mochamad Alfan; Suprianto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background : Augmented Reality (AR) has become a promising tool for enhancing visualization in mathematics education, particularly in learning three-dimensional geometry. Specific Background: Students at SDN Sidoklumpuk experience difficulties understanding spatial forms due to limited physical teaching aids. Gap: Existing AR-based studies rarely integrate visualization, formulas, and interactive assessment in a single application tailored for elementary learners. Aims: This study aims to design an AR-based learning application using Unity 3D and Vuforia SDK to support students’ understanding of geometric solids. Results: The application presents 3D objects, displays formula explanations, and provides a Mini Quiz feature. Black-box testing shows that all functions operate successfully, and early classroom trials indicate improved student engagement and comprehension. Novelty: The integration of AR visualization with formula assistance and in-app assessment offers a more complete learning tool than typical AR implementations. Implications: The application can support teachers in delivering abstract geometry concepts and can be expanded for broader curriculum use. Highlights Visualization of 3D geometric solids using AR Integrated formula display and interactive quiz Designed specifically for elementary mathematics learning Keywords: Augmented Reality, Geometry Learning, Unity 3D, Multimedia Development Life Cycle, Elementary Education